Scythian Antiquities in Western Asia - Sulimirski, T.
1. The Appearance of the Scythians — 2. Early Scythians in Western Asia — 3. Scythian Archaeological Remains in Western Asia (Western Asia, Caucasus, Asia Minor and Islands, Greece, Egypt, Western Mediterranean, Western Europe) — 4. Origin of the “Scythian” Arrow Heads — 5. Oriental Elements in the Pontic Scythian Culture — 6. Origin of the Pontic Scythian Culture.